OTU-014 Reproductive factors and risk of gastric cancer by anatomical subsite: the epic study. (8th June 2018) - Sanikini, Harinakshi; Gunter, Marc; Agudo, Antonio; Duell, Eric; Riboli, Elio; Cross, Amanda
Abstract : Introduction: Gastric cancer is more common in men than in women, indicating a potential role for sex hormones in its development. The aetiology of gastric cancer differs by anatomical subsite; however, few studies have compared hormonal and reproductive risk factors by subsite in prospective analyses. We investigated the association between reproductive factors and the risk of gastric cancer by subsite in the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort. Methods: EPIC is an on-going multicentre prospective cohort study, which comprises of 5 21 448 men and women, aged 25–70 years, recruited between 1992–2000 from ten European countries. Questionnaires administered at baseline assessed reproductive factors, including age at menarche, menopause, first pregnancy, and first child birth, as well as parity, breast feeding, menopausal hormonal therapy, and oral contraceptive use. The association between reproductive factors and gastric cancer were examined in Cox proportional hazard models to estimate hazard ratios (HRs) and 95% confidence intervals (CIs), adjusting for potential confounders. Results: During an average of 14 years of follow up, 83 gastric cardia cancers and 191 gastric non-cardia cancers were diagnosed among 3 43 985 women. Compared to women who had their first pregnancy at an earlier age (<22 years), women who had their pregnancy at a later age (>26 years) had a decreased risk of gastric non-cardia cancer (HR 0.55, 95% CI: 0.32–0.92). In addition, compared with women who had not undergone ovariectomy, women who had a bilateral ovariectomy had an increased risk of gastric non-cardia cancer (HR 1.83, 95% CI: 1.02–3.28). For gastric cardia cancer, there was also an elevated risk among women who had a bilateral ovariectomy but this did not quite attain statistical significance (HR 2.19, 95% CI: 0.98–4.86). The remaining reproductive factors analysed were not associated with risk of gastric cardia or non-cardia cancer. Conclusion: The results of this study suggest that reproductive factors in women may influence risk for gastric cancer, particularly non-cardia gastric cancer.